INTEGRATION OF AUGMENTED REALITY TECHNOLOGY IN MATHEMATICS LEARNING: IMPACT ON CONCEPTUAL UNDERSTANDING - J. R. Stephanus (Penelitian dan Pengembangan Ilmu, 2025)
Mathematics learning often faces significant challenges due to the abstract nature of its concepts, causing difficulty in understanding and anxiety in students. Conventional methods have proven ineffective in addressing this issue, prompting the exploration of pedagogical innovations. This study aims to explore the effectiveness of Augmented Reality (AR) integration in mathematics learning on students' conceptual understanding compared to conventional methods. Using a thematic synthesis approach, this systematic literature review analyzes articles.peer-reviewedA study from Scopus, Web of Science, ERIC, and Google Scholar (2013–2025) compared AR with traditional learning. The results showed that AR significantly improved conceptual understanding, particularly in visual-abstract topics such as three-dimensional geometry and functions, through interactive visualization and reduced cognitive load. However, its effectiveness varied depending on instructional design, technological readiness, and institutional support. The conclusions emphasize that AR is not simply a visual tool, but rather an innovation capable of supporting cognitive processes and experiential learning. Practical implications emphasize the need for planned AR integration and adequate teacher training to maximize the potential of this technology in improving the quality of mathematics learning.